2023
DOI: 10.1101/2023.01.05.23284236
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Significance of Wastewater Surveillance in Detecting the Prevalence of SARS-CoV-2 Variants and Other Respiratory Viruses in the Community – A Multi-Site Evaluation

Abstract: Detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) viral genome in wastewater has proven to be useful for tracking the trends of virus prevalence within the community. The surveillance also provides precise and early detection of any new and circulating variants, which aids in response to viral outbreaks. Site-specific monitoring of SARS-CoV-2 variants provides valuable information on the prevalence of new or emerging variants in the community. We sequenced the genomic RNA of viruses pre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
0
4
0
1
Order By: Relevance
“…This differentiation was observed consistently across all four methods. These temporal shifts in virus composition may suggest a temporally variable metavirome composition in wastewater, potentially influenced by changes in circulating viruses 8, 48, 49 and changing wastewater conditions, such as flow rate, total suspended solids (TSS), total organic compounds (TOC), and the abundance of antagonistic microorganisms 50, 51 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This differentiation was observed consistently across all four methods. These temporal shifts in virus composition may suggest a temporally variable metavirome composition in wastewater, potentially influenced by changes in circulating viruses 8, 48, 49 and changing wastewater conditions, such as flow rate, total suspended solids (TSS), total organic compounds (TOC), and the abundance of antagonistic microorganisms 50, 51 .…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the choice of probe panel likely also impacts the sensitivity of virus detection in probe-capture sequencing. When using the RVOP probe set (which contains fewer virus targets than the VSP probe set) several studies found remarkably high coverages of SARS-CoV-2, surpassing that of other human viruses included in the RVOP panel 14, 15, 49 . However, in the present study and other studies using broad virus capture panels 23, 48 , sequence data were dominated by enteric viruses such as mamastrovirus, with limited detection of SARS-CoV-2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study included 7 local sub-sewershed and 3 WRF sites, ranging from the Southern Truckee Meadows region to the Northern Reno-Stead region. 13,14 Collectively, these sites represent in uent from over 450,000 residents. The largest sample site is the Truckee Meadows WRF (TMWRF).…”
Section: Sample and Study Sitesmentioning
confidence: 99%
“…De forma complementaria a la detección clínica, la vigilancia ambiental de los virus, especialmente los relacionados con la viabilidad y la potencial infectividad como el SARS-CoV-2, podría actuar como una herramienta útil para predecir brotes oportunos de enfermedades y emitir una alerta rápida por parte de las autoridades sanitarias (12,13) . En ese sentido, las muestras de aguas residuales son una fuente de información no invasiva y económica para investigar la propagación de diferentes variantes genéticas del SARS-CoV-2 dentro de una comunidad (14,15) . La secuenciación masiva y el análisis metagenómico nos permitirían detectar el virus e identificar las variantes circulantes del SARS CoV-2 al mismo tiempo.…”
Section: Introductionunclassified